Knowledge, Perceptions, and Attitudes Toward Contraceptive Medicine among Undergraduate Students in Southern Vietnam - Quang Vo, Dr. Trung (Asian Journal of Pharmaceutics (AJP), 2018)
Aims: This study examined the knowledge, attitudes, and perceptions of Vietnamese university students regarding various contraceptive methods. Materials and Methods: The cross-sectional descriptive study was conducted from March 2017 to May 2017. A pre-tested self-administered questionnaire was used to collect the necessary data, including general information as well as the participants’ knowledge, awareness, perceptions, and intention regarding contraceptives. Statistical Analysis used: The Chi-square, Kruskal–Wallis, and Mann–Whitney U-tests were manipulated to calculate the association between the study variables. Results: Of the 1,107 respondents, 100% had previously heard about different contraceptive methods. The results showed that the contraceptive-related knowledge of medical students was higher than that of non-medical students (P < 0.001). The majority of participants exhibited a good level of awareness and positive perceptions regarding contraceptives. Some 60% of participants revealed that they would use contraceptives in the future if needed, which indicated a positive attitude and a strong tendency to use contraceptive methods in the future. However, the findings show that the majority of students had inadequate knowledge, awareness, and perceptions about contraceptives. It is hence necessary to develop and provide relevant health education to better empower young people. Conclusions: Both the knowledge and awareness of contraceptives among Vietnamese university students are low, while the number of misperceptions is high. This study will contribute to efforts focusing on providing reproductive health education and counseling, as well as demonstrating the importance of using reliable means of communication.